Mild and General Palladium-Catalyzed Synthesis of Methyl Aryl Ethers Enabled by the Use of a Palladacycle Precatalyst - Cheung, Chi Wai (2013)
[Image: see text] A general method for the Pd-catalyzed coupling of methanol with (hetero)aryl halides is described. The reactions proceed under mild conditions with a wide range of aryl and heteroaryl halides to give methyl aryl ethers in high yield.